Correction Alternative mechanisms of miR-34a regulation in cancer - Slabáková, Eva; Culig, Zoran; Remšík, Ján; Souček, Karel (Cell death & disease, 2018)
The PDF and HTML versions of the article have been updated to include the Creative Commons Attribution 4.0 International License information.